Edukasi Penerapan Personal Higiene pada Pekerja dan Sanitasi Depot Air Minum Isi Ulang - Fea Firdani; Azyyati Ridha Alfian; Vivi Sutia Desmalinda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
There has been an increase in the number of refilled drinking water depots (DAMIU) yearly because they answer most people's needs in urban areas. Implementing hygiene and sanitation management at DAMIU is critical because it affects the quality of drinking water consumed by the public. The community engagement activities were carried out in stages at 25 depots located in the working area of the Andalas Community Health Center from June to July 2023. The method used was providing education regarding hygiene and sanitation requirements. Refill by statutory regulations and provide equipment for implementing personal hygiene to supply drinking water depot workers as well as making posters that will be posted at each refill drinking water depot, which is a community service partner regarding the implementation of personal hygiene and sanitation at refill drinking water depots. Evaluation of the activities results shows increased workers' knowledge regarding the importance of implementing personal hygiene while working. It is hoped that educational media can increase workers' compliance in implementing personal hygiene and sanitation while working.